SISTEM PAKAR DIAGNOSIS PENYAKIT KUCING BERBASIS WEB MENGGUNAKAN METODE FORDWARD CHAINING PADA 88 VET CLINIC - Dani, Dani; Solikin, Solikin (JURNAL MAHASISWA BINA INSANI; Vol 8 No 1 (2023): Jurnal Mahasiswa Bina Insani (Agustus 2023), 2023)
Cats are animals that are loved by various groups of people and ages, not a few people keep cats as pets. Maintaining cat health is the most important thing in keeping a pet cat. Lack of information about cat diseases and also a lack of awareness about the importance of maintaining health in cats results in many cats that are not healthy. With this disease, it requires the help of an expert who understands cat disease. So we need an application that can help and solve problems. The system design used is the web-based forward chaining method and the application design used is extreme programming. The expected result from this research is an expert system application that can help the customer to find out diseases quickly to take action on pet cats.